Faktor-Faktor Yang Berhubungan dengan Motivasi Petani Menanam Mangrove Di Desa Mayangan Kecamatan Gumukmas Kabupaten Jember, Jawa Timur - Ridlo Wahyudi; Lenny Widjayanthi; Sri Subekti (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this research is to find out factors related to farmer's motivation to grow mangrove in Mayangan Village, Gumukmas Sub-district, Jember District. The method used in this study uses descriptive and correlational methods. The result of the analysis shows that the variables of experience, formal education and non-formal education have a relationship with the motivation of farmers to plant mangrove while other variables such as age and number of family members have no relationship, at 95% confidence level.